2020
DOI: 10.3390/metabo10030111
|View full text |Cite
|
Sign up to set email alerts
|

Compound Characterization and Metabolic Profile Elucidation after In Vitro Gastrointestinal and Hepatic Biotransformation of an Herniaria hirsuta Extract Using Unbiased Dynamic Metabolomic Data Analysis

Abstract: Herniaria hirsuta L. (Caryophyllaceae) is used for treatment of urinary stones and as a diuretic. Little is known about the active compounds and the mechanism of action. The phytochemical composition of H. hirsuta was comprehensively characterized using UHPLC-UV-HRMS (Ultrahigh-Performance Liquid Chromatography-Ultraviolet-High Resolution Mass Spectrometry) data. An in vitro gastrointestinal model was used to simulate biotransformation, which allowed the monitoring of the relative abundances of individual comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…From a pharmacological point of view, the aqueous extract of the aerial part of this plant has an inhibitory effect on the crystallization of calcium oxalate in vitro at doses of 0.0625 mg/mL and 0.5% of plant extracts in physiological solution (9 g of NaCl /L) [ 96 , 97 ], and in vivo at a concentration of 50 mg/mL [ 98 ], also has an effect on cystine stones in different patients with congenital cystinuria at a dose of 20 g/L [ 101 ]. Phytochemical studies have reported and identified some components of H. hirsuta include flavonoids, coumarin, tannins and saponins [ 100 , 171 , 172 , 173 ]. The active component in the prevention of lithiasis has not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From a pharmacological point of view, the aqueous extract of the aerial part of this plant has an inhibitory effect on the crystallization of calcium oxalate in vitro at doses of 0.0625 mg/mL and 0.5% of plant extracts in physiological solution (9 g of NaCl /L) [ 96 , 97 ], and in vivo at a concentration of 50 mg/mL [ 98 ], also has an effect on cystine stones in different patients with congenital cystinuria at a dose of 20 g/L [ 101 ]. Phytochemical studies have reported and identified some components of H. hirsuta include flavonoids, coumarin, tannins and saponins [ 100 , 171 , 172 , 173 ]. The active component in the prevention of lithiasis has not yet been identified.…”
Section: Resultsmentioning
confidence: 99%
“…The active component in the prevention of lithiasis has not yet been identified. However, the literature suggests that the antilithiatic potential of H. hirsuta is attributed to saponins with a high probability [ 171 , 174 ]. Recently, a phytochemical study conducted to identify the bioactive constituents of H. hirsuta has shown that the aerial part of this plant is rich in phenolic compounds ( Figure 7 a,b) [ 171 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though a lot of research has been done to prove the activity of H. hirsuta against urolithiasis, little is known about the active compounds and the exact mechanism of action. Previous phytochemical research on Herniaria species revealed the presence of saponins, flavonoids and coumarins (Charrouf et al, 1996;Mbark et al, 1995;MBark et al 1996, van Dooren et al, 2016Peeters et al, 2020a). Literature suggests that the antilithiatic potential of H. hirsuta is attributed to saponins or metabolites thereof (van Dooren et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Monitoring of metabolite formation during in vitro gastrointestinal biotransformation studies of an extract of H. hirsuta showed an increase in formation of saponin aglycones, with medicagenic acid as the most abundant one. Medicagenic acid was further biotransformed in an in vitro hepatic model into several phase I and II metabolites (Peeters et al, 2020a;Peeters et al, 2020b). The aim of this study was to evaluate the in vitro effect of these metabolites on calcium oxalate crystallization and crystal-cell interaction.…”
Section: Introductionmentioning
confidence: 99%